Islamic Perspective of Anti-Violence Education for Early Childhood in The Family Environment - Zahroh, Luluk Atirotu (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
Anti-violence education implemented in various educational environment, equally important the family environment. The impact of violence against spiritual emotional intelligence development of children leads to the negative things. Include that realize or not, violence that showed by parents have instilled hatred and excessive fear in children. Violence will infuse stubborn and rude in children, give wound in the hearts of children until they are adults. Islam teaches anti-violence education, especially on the early chilhood education, have to carry out with great affection. Many verses of the holy Koran which instruct to educate children with affection. The term like qaulan layyinan, qaulan marufan and so on are some command to teach and interact with students full with love and through the good ways. Keyword: anti-violence education, early chilhood. Pendidikan anti kekerasan diterapkan di berbagai lingkungan pendidikan, dan tidak kalah pentingnya yaitu lingkungan keluarga. Dampak kekerasan orang tua terhadap perkembangan kecerdasan emosional spiritual anak ini mengarah pada hal-hal yang negatif. Dampak tersebut diantaranya adalah: sadar atau tidak kekerasan yang dilakukan orang tua telah menanamkan kebencian dan rasa takut yang berlebihan pada diri anak. Kekerasan akan menanamkan sifat keras dan sikap kasar pada diri anak, membekaskan luka di hati anak hingga mereka dewasa. Islam mengajarkan pendidikan yang bersifat anti kekerasan, apalagi dalam konteks mendidik anak usia dini, dilakukan dengan penuh kasih sayang. Banyak ayat al-Qurâan yang memerintahkan mendidik anak dengan kasih sayang kepada putra-putranya yang masih kecil. Bahasa qaulan layyinan, qaulan maârufan dan sebagainya merupakan perintah untuk mendidik dan berinteraksi dengan anak didik dengan penuh kasih sayang dan cara yang baik. Kata Kunci: Pendidikan Anti Kekerasan, Anak Usia Dini.